The Roles of School Principal in the Implementation of Character Education at Boarding School - Asmendri, Asmendri (AT-TALIM, 2014)
The success or failures of educational institutions in the implementation of character education in boarding schools or madrasah is determined by its leaders.Â  The school principal as a leader and educator should be a good model to all teachers and learners in the school. Â In other words,Â  he or she will create a healthy school life, conducive and supportive school performance. There are seven principalâs roles in implementing character building the school. He or she should has a clear vision, rely on more collaborative approach,Â  responsive and proactive in responding to what is happening outside of school, be consistent in enforcing the rules, be active, give Â many social rewards, and create a variety of rides or activities that can develop pro-social skills and devotion of students.